KAJIAN PEGGUNAAN BERBAGAI JENIS BIOBRIKET SEBAGAI ALTERNATIF PENGGANTI MINYAK TANAH UNTUK RUMAH TANGGA - Budiyanto Budiyanto; Pandu Imam Sudibyo Adib; Sari Puspita Ningsih (BPFP Faperta UNIB, 2011)
Biobriquet defined as fuel and solid which came from organic rested material. The formation of biomass into biobriquet intended to facilitate its utilizing. The use of biobriquet as alternative energy can replace the use of kerosene for burning needs in the household. This research is aimed to determine the best type of biobriquet based on the quality of burning performance produced by kerosene control and determine life time of biobriquet that have been packaged on plastic and paper bags that saved in temperature room. This research was conducted in the Laboratory of Agricultural Technology, Faculty of Agriculture,UniversityofBengkuluand PT Sucofindo Bengkulu. It examined four types of biobriquet which are palm shell charcoal biobriquet (A), Empty fruit bunch (EFB) charcoal + coal biobriquet (B), EFB charcoal biobriquet (C) and non-choarcoling oil palm shells biobriquet (D). Observed variables are the calorific value, moisture content, ash content, levels of substance to fly, lighting time, burning time, Water Boiling Test (WBT), Control Cooking Test (CCT), intensity of smoke, and water content changes in packaging of biobriquet. The results showed that non-choarcoling palm oil shells biobriquet (D) is the best biobriquet based on performance quality. If it compared with kerosene, non-choarcoling palm oil shells biobriquet (D) is better than kerosene, while in other biobriquets, kerosene is still the best one. Based on other biobriquet tests (water content, calorific value, ash content, levels of substance to fly, lighting time, burning time and fuel consumption biobriquet), the best biobriquet that replaced kerosene is TKKS charcoal biobriquet (C), however, for the variables which compared with kerosene (burning time and fuel consumption), kerosene is still the best one. Biobriquet that packaged by using paper bags for 6 weeks the rising of water levels are relatively low compared with the plastic bags.